What is the Way Allah's Word Manifests Itself in Yemeni Arabic? - Yousef Ali Ahmed Saleh Al-Nahdi; Yenni Patriani; Zhao Shuo; Fuzhen Si (Institut Agama Islam Negeri Bengkulu, 2022)
In this paper, the author shows how ‘Allah’ is used in daily Yemeni Arabic conversations. The term Allah has a variety of meanings in Yemeni Arabic, as it does in the Arab world, reflecting the belief that Allah alone is in charge of all the affairs, grants blessings, and either encourages or criticizes someone to do something. The result of this is that the term Allah appears in several expressions when the term is part of a sentence containing the word. For example, there are expressions that have over one meaning, such as Allah alaik, which signifies two literal meanings. The word Allah can also be found in other expressions, but with entirely different meanings, including moaning or aiming for guidance. I conducted a study looking at the occurrences of social life contact, reactions, and the cultural influence of native Yemenis. The rest of this paper explores some of the other most common expressions used in Yemeni society, which shows the word is heavily influenced by religion and culture in its use in Yemeni society.